Gender Impact of Interregional Trade: The Case of EU-Mercosur Relations - Pavese, Carolina (Latin American Journal of Trade Policy, 2021)
After two decades of negotiations, the European Union (EU) and Mercosur celebrated a new Association Agreement in 2019. Structured around three pillars (political dialogue, cooperation, and trade), the deal is still pending ratification but has raised strong criticism. Most concerns address the effect of trade liberalization on social and environmental agendas. This article contributes to this debate, conducting qualitative analysis on the agreement’s potential impact on gender equality in the EU and Mercosur. Departing from the feminist scholarship assumption that trade has an unavoidable effect on gender, this article argues that interregional trade agreements can be a helpful policy instrument to promote gender equality. Nevertheless, this research demonstrates that, so far, the EU-Mercosur Association Agreement has neglected this opportunity. The provisional text does not reflect a gender mainstreaming approach, lacking the appropriate mechanisms to manage its effects on women. As a result, the new interregional trade liberalization instrument risks widening gender inequality in both regions. Nevertheless, this research demonstrates that, so far, the EU-Mercosur Association Agreement has neglected this opportunity. The provisional text does not reflect a gender mainstreaming approach, lacking the appropriate mechanisms to manage its effects on women. As a result, the new interregional trade liberalization instrument risks widening gender inequality in both regions.